STRATEGY MAP BALANCED SCORECARD: SISTEM MANAJEMEN UNTUK IMPLEMENTASI STRATEGI PERUSAHAAN (STUDI KASUS PT ERRATISA PURNAMA) - Trias Pratiwi, Yoshi; Rodhiyah, . (Buletin Studi Ekonomi; VOL.20.NO.1.FEBRUARI 2015 (PP 1-82), 2016)
Strategy Map of Balanced Scorecard: Management System for Company Strategy Implementation (Study Case of PT Erratisa Purnama) PT Erratisa Purnama engaged in the school uniforms production and trading. Existing planning systems rely on a budget, it is not sufficient to maintain the viability of the organization in a competitive & complex business environment. Therefore, the company’s vision, mission, and strategy need to be translated into a balanced scorecard management system. The research objective is to design a strategy map for PT Erratisa Purnama in explaining the strategic objectives and the process of value creation. Further more to design performance benchmarks in translating the strategic objectives (contained in the strategy map) to the measures, targets, and initiatives. The approach used in this study is a qualitative explanatory approach which explains how to design a balanced scorecard management system in the company so that the final results of this study apply to companies surveyed only.   Keywords: strategy map, balanced scorecard, strategy of company
Keywords: strategy map, balanced scorecard, strategy of company